2014
DOI: 10.4103/2230-8598.127168
|View full text |Cite
|
Sign up to set email alerts
|

High-risk human papillomavirus infection among women with pap smear tests negative for intraepithelial lesions or malignancy

Abstract: High-risk human papillomavirus infection among women with pap smear tests negative for intraepithelial lesions or malignancyCervical cancer is one of the most common cancers in United Arab Emirates (UAE) as well as in the world; high-risk human papillomavirus (HR-HPV) infection is found to be the most common cause of cervical cancer. The objective of the study is to evaluate the status of HR-HPV infection among women with Pap smear tests negative for intraepithelial lesions/malignancy (NILM). This cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…These patients with normal Pap tests and HR-HPV types must be regularly followed up in accordance with international guidelines. This is because of the fact that women with HR-HPV positivity and negative Pap smear tests for intraepithelial lesions are at a high risk of having serious HPV induced lesions in the future [31]. Delayed follow-up may have jeopardized these patients at risk for serious epithelial changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These patients with normal Pap tests and HR-HPV types must be regularly followed up in accordance with international guidelines. This is because of the fact that women with HR-HPV positivity and negative Pap smear tests for intraepithelial lesions are at a high risk of having serious HPV induced lesions in the future [31]. Delayed follow-up may have jeopardized these patients at risk for serious epithelial changes.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly HPV genotyping performed by the F-HPV typing™ multiplex PCR (Molgentix SL, Barcelona, Spain). The assay uses 16 specific primers amplifying within E6 and E7 regions of the HPV genome and permits the detection of 13 high risk genotypes (16,18,31,33,35,39,45, 51, 52, 56, 58, 59 and 68) and two low-risk genotypes (6 and 11). The presence of DNA of these HPV subtypes were detected by multiplex PCR amplification using type specific primers [14,15].…”
Section: Dna Isolation and Hpv Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…The early age of marriage [34] and the high fecundity index in UAE (estimated to be 2.37 children/women in 2013) [35], with the subsequent modulation of the immune response to HPV might be contributing factors to these figures [36]. It is important to stratify the age patterns in relation to prevalence of HPV to help create the proper preventive screening protocols relevant to the community [22].…”
Section: Variablesmentioning
confidence: 97%
“…A very low rate of cervical cancer screening tests is reported across literatures in low and middle-income countries [15,[19][20][21][22]. A study on health-seeking behavior of patients with cervical cancer in Ethiopia also revealed that women had a very low awareness of cervical cancer and they mostly prefer traditional remedies as a treatment option for the early stages of the disease.…”
Section: Introductionmentioning
confidence: 99%